Effect of Distraction Technique During Immunization to Reduce Behaviour Response Score (FLACC) to Pain in Toddlers - Gedam, DS; Verma, M; Patel, U; Gedam, S (Journal of Nepal Paediatric Society, 2013)
Introduction: Distraction techniques are important non pharmacological tools to reduce pain in infants and children. Few data are available regarding their effectiveness in toddlers. We have assessed effectiveness of audio-visual distraction techniques in toddlers during and after vaccination. Materials and Methods: The study used a quasi experimental three group pretest post test design. For all the three groups, the injections were administered by same staff nurse. Group- 1 (120 Patient) was encouraged to see and play with light and sound producing toy. Group- 2 (120 Patient) children were encouraged to see cartoon movie and children of control group- 3 (110 patient) were immunized without any distraction technique. A question form was used to determine the infant’s characteristics and the Face, Leg, Activity, Cry, Consolability (FLACC) Pain Scale was used to assess the level of pain. Data was collected between 1st April 2012 and 30th September 2012. Results: The mean pain score of test group during procedure (Group-1: 2.30 & Group-2: 3.65) were lower than the score of control group (Group-3: 5.30). Similarly after procedure Score (Group-1: 4.62 & Group-2: 2.79) were lower than the score of control group (Group-3: 6.20). Conclusion: The lower pain score in response to vaccination in test group indicates that distraction technique i.e. light & sound producing toys and cartoon movies are practical way to reduce pain during routine medical interventions in toddler. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7017 J Nepal Paediatr Soc. 2013;33(1):25-30